2009
DOI: 10.1186/1754-6834-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Parallel metatranscriptome analyses of host and symbiont gene expression in the gut of the termite Reticulitermes flavipes

Abstract: Background: Termite lignocellulose digestion is achieved through a collaboration of host plus prokaryotic and eukaryotic symbionts. In the present work, we took a combined host and symbiont metatranscriptomic approach for investigating the digestive contributions of host and symbiont in the lower termite Reticulitermes flavipes. Our approach consisted of parallel high-throughput sequencing from (i) a host gut cDNA library and (ii) a hindgut symbiont cDNA library. Subsequently, we undertook functional analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
250
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(270 citation statements)
references
References 96 publications
(151 reference statements)
17
250
1
2
Order By: Relevance
“…61) This appears to parallel a recent report that lignin degradation was observed in the gut of the termite Z. angusticollis, 62) but it has been found that homologous laccase genes in the genomes of various insects are involved in tanning cuticles. 63) Since the sequencing efforts in these metatranscriptomic analyses were too weak to be useful to predict the entire functions of the protistan microbiota, more exhaustive analysis is needed.…”
Section: Metagenomics and Metatranscriptomics Of Termite Gut Micsupporting
confidence: 72%
“…61) This appears to parallel a recent report that lignin degradation was observed in the gut of the termite Z. angusticollis, 62) but it has been found that homologous laccase genes in the genomes of various insects are involved in tanning cuticles. 63) Since the sequencing efforts in these metatranscriptomic analyses were too weak to be useful to predict the entire functions of the protistan microbiota, more exhaustive analysis is needed.…”
Section: Metagenomics and Metatranscriptomics Of Termite Gut Micsupporting
confidence: 72%
“…Until recently, metatranscriptomics had been limited to the microarray/high-density array technology (46,86,140) or analysis of mRNA-derived cDNA clone libraries (90,119). These approaches have produced significant insights into the gene expression of microbial communities but have limitations.…”
Section: Metatranscriptomicsmentioning
confidence: 99%
“…In the mammalian gut, the diversity of bacteria increases according to host diet, from carnivores to omnivores to herbivores (38). The intestinal bacteria of insects such as termites and aphids produce compounds that are essential and otherwise inaccessible for the host (e.g., detritus, phloem, sap, wood, and xylem) (28,63,64). Most studies on the relationships between insect diet and the distribution of gut microbiota have tended to focus on specific microbes in a single insect group; however, a recent, wider-ranging study based on previously published and newly generated 16S rRNA gene sequences from 62 insect species from seven orders reported that both host diet and taxonomy affect insect gut bacterial communities (12).…”
Section: Figmentioning
confidence: 99%